Paraganglioma: A Multidisciplinary Approach - Mariani-Costantini, Renato (Exon Publications, 2019)
Paragangliomas and pheochromocytomas are rare tumors of the autonomic nervous system that represent a diagnostic and therapeutic challenge. While the classic sites of origin are the adrenal medulla and the autonomic branches of the lower cranial nerves, they may arise from any site in connection with the autonomic neural branches in the thoracic, abdominal, and head and neck regions. The uncontrolled release of catecholamines by these tumors can be life-threatening. Paragangliomas and pheochromocytomas are the tumor types in which the impact of genetic predisposition factors is the highest. The treatment of paraganglioma and pheochromocytoma requires specialized knowledge and solid experience, which, given the rarity of these diseases, is available only in highly specialized centers. This book includes specific chapters written by experts from several countries that deal with relevant aspects of paraganglioma and pheochromocytoma diagnosis and therapy. Chapter 1 addresses the genetic findings that are most relevant to diagnosis and management, chapter 2 deals with the biochemical diagnosis, chapter 3 with imaging, chapter 4 with the surgical and pharmacological management, mainly of trunk paraganglioma and pheochromocytoma, chapters 5 and 6 with the histopathological, genetic, and clinical characteristics of carotid body, and vagal and tympano-jugular paragangliomas.